Gravitational redshifting of galaxies in the SPIDERS cluster catalogue. Issue 1 (26th February 2021) - Mpetha, C T; Collins, C A; Clerc, N; Finoguenov, A; Peacock, J A; Comparat, J; Schneider, D; Capasso, R; Damsted, S; Furnell, K; Merloni, A; Padilla, N D; et al.
ABSTRACT: Data from the SPectroscopic IDentification of ERosita Sources (SPIDERS) are searched for a detection of the gravitational redshifting of light from 20 000 galaxies in ∼2500 galaxy clusters using three definitions of the cluster centre: its Brightest Cluster Galaxy (BCG), the redMaPPer identified Central Galaxy (CG), or the peak of X-ray emission. Distributions of velocity offsets between galaxies and their host cluster's centre, found using observed redshifts, are created. The quantity Δ , the average of the radial velocity difference between the cluster members and the cluster systemic velocity, reveals information on the size of a combination of effects on the observed redshift, dominated by gravitational redshifting. The change of Δ with radial distance is predicted for SPIDERS galaxies in General Relativity (GR), and f ( R ) gravity, and compared to the observations. The values of Δ =-13.5± 4.7 km s −1, Δ =-12.5± 5.1 km s −1, and Δ =-18.6± 4.8 km s −1 for the BCG, X-ray, and CG cases, respectively, broadly agree with the literature. There is no significant preference of one gravity theory over another, but all cases give a clear detection (>2.5σ) of Δ . The BCG centroid is deemed to be the most robust method in this analysis, due to no well-defined central redshift when using an X-ray centroid, and CGs identified by redMaPPer with no associated spectroscopic redshift. For future gravitational redshift studies, an order-of-magnitude more galaxies, 500 000, will be required – a possible feat with the forthcoming Vera C. Rubin Observatory, Euclid and eROSITA .